2012
DOI: 10.3109/09637486.2012.734288
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between emotions and food consumption (macronutrient) in a foodservice college setting – a preliminary study

Abstract: Many aspects of eating out have been studied, yet emotions remain an under-researched area, despite having been shown to play a significant role in food consumption. The aim of this research is to critically evaluate the relationship between emotions and food consumption (macronutrient) in a realistic eating environment, a college cafeteria. Subjects (n = 408), diners using a cafeteria, completed an emotions questionnaire before and after freely choosing, paying for and consuming a hot main meal. The results d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Most literature on emotion research has shown that women tend to be more emotional than men (e.g., Diener, Sandvik, & Larsen, 1985). That said, although the food-related research to date has mainly examined emotion responses to single food stimuli, and not mealtimes, findings suggest that the experience of positive emotional responses (happiness) to food images may be higher for men than for women (e.g., Hartwell et al, 2013;McNamara, Hay, Katsikitis & Chur-Hansen, 2008). Previous literature has also shown that men tend to have more positive associations towards hot meal-related foods than women, who would prefer uncooked or snack-related items as comfort foods.…”
Section: Discussion Of Findings Linked To Rq1 Rq2 and Rq3mentioning
confidence: 94%
“…Most literature on emotion research has shown that women tend to be more emotional than men (e.g., Diener, Sandvik, & Larsen, 1985). That said, although the food-related research to date has mainly examined emotion responses to single food stimuli, and not mealtimes, findings suggest that the experience of positive emotional responses (happiness) to food images may be higher for men than for women (e.g., Hartwell et al, 2013;McNamara, Hay, Katsikitis & Chur-Hansen, 2008). Previous literature has also shown that men tend to have more positive associations towards hot meal-related foods than women, who would prefer uncooked or snack-related items as comfort foods.…”
Section: Discussion Of Findings Linked To Rq1 Rq2 and Rq3mentioning
confidence: 94%
“…Among adult catering guests, the eating of a hot meal was found being related to personal emotions by generally flattening positive and negative premeal emotions (Edwards, Hartwell, & Brown, ). Especially negative pre‐meal emotions significantly decreased after a hot meal and appeared being switched toward general feelings of contentment if food was either high in fat or protein (Hartwell, Edwards, & Brown, ). Accordingly emotional benefits of food may stand against recommendations for meal options that generally are considered healthy with low energy‐density (Hartwell et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Especially negative pre‐meal emotions significantly decreased after a hot meal and appeared being switched toward general feelings of contentment if food was either high in fat or protein (Hartwell, Edwards, & Brown, ). Accordingly emotional benefits of food may stand against recommendations for meal options that generally are considered healthy with low energy‐density (Hartwell et al, ). In line with this, Stroebele and de Castro () could relate larger meal intakes in different settings to subjectively perceived arousal of students and Paquet, St‐Arnaud‐McKenzie, Kergoat, Ferland, and Dubé () found for elderly persons that positive emotions at mealtime are related to higher energy and protein intakes which may be related to changes in ‘perceptual and environmental judgements’ (p. 156).…”
Section: Resultsmentioning
confidence: 99%
“…The problem of relationship between emotions with the consumption of food is very often studied area [9,10,11]. In presented study, it have showed that both positive and negative emotions are related to eating behaviour.…”
Section: Discussionmentioning
confidence: 78%
“…There are a number of studies which have shown relationship between emotions and food consumption [9,10,11]. The analysis of the relationship between positive emotional state and eating behaviour was not tested too often.…”
Section: Introductionmentioning
confidence: 99%